The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1161/atvbaha.111.224139
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of How rs7575840 Influences Apolipoprotein B–Containing Lipid Particles

Abstract: Objective-Recent genome-wide association studies identified a variant rs7575840 in the apolipoprotein B (APOB) gene region as associated with low-density lipoprotein (LDL) cholesterol. However, the underlying functional mechanism of this variant, which resides 6.5 kb upstream of APOB, has remained unknown. Our objective was to investigate rs7575840 for association with refined apoB-containing lipid particles, for replication in a Mexican population, and for its underlying functional mechanism. Methods and Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 22 publications
0
9
0
2
Order By: Relevance
“…Apolipoprotein B (APOB) is the main apolipoprotein of chylomicrons, very low density lipoproteins, and low density lipoproteins and is highly expressed in liver and small intestine as long (ApoB100) and short (ApoB48) isoforms, respectively, via RNA editing of the same transcript. The role of APOB in other tissues is not clear; however, Hass et al (2011) showed that a serum LDL-C associated SNP rs7575840 is a cis-eSNP for the expression of APOB mRNA in adipose tissue of European Ancestry individuals 34 . Replicating this finding, the T-allele of rs7575840 was associated with higher expression of APOB in adipose tissue of African American individuals of our AAGMEx cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Apolipoprotein B (APOB) is the main apolipoprotein of chylomicrons, very low density lipoproteins, and low density lipoproteins and is highly expressed in liver and small intestine as long (ApoB100) and short (ApoB48) isoforms, respectively, via RNA editing of the same transcript. The role of APOB in other tissues is not clear; however, Hass et al (2011) showed that a serum LDL-C associated SNP rs7575840 is a cis-eSNP for the expression of APOB mRNA in adipose tissue of European Ancestry individuals 34 . Replicating this finding, the T-allele of rs7575840 was associated with higher expression of APOB in adipose tissue of African American individuals of our AAGMEx cohort.…”
Section: Discussionmentioning
confidence: 99%
“…As an example, maternal allele-specific association of a common variant (rs1367117) located in the APOB gene was demonstrated in the analysis of adiposity [17] and borderline significant effect for fasting glucose and insulin levels [17]. This nonsynonymous missense variant that cause a Thr > Ile amino acid change was also observed in non-POE association with serum ApoB levels [18].…”
Section: Aimmentioning
confidence: 93%
“…The METSIM study data has been helpful in generating functional information for some GWAS variants, e.g., a variant rs7575840 in the APOB gene region associated with LDL cholesterol level. Adipose tissue RNA expression analysis indicated that rs7575840 alters the expression of APOB and a regional noncoding RNA (BU630349) (76). Another study examined the functional regulatory effects of 25 noncoding variants at the GALNT2 locus associated with HDL cholesterol in the METSIM cohort.…”
Section: Functional Studiesmentioning
confidence: 99%